The Works of Li Qingzhao - Allen, Sarah M. (Library of Chinese Humanities, 2019)
This volume is a translation of the song lyrics, poetry, and prose of Li Qingzhao (1084-1150s), with annotations and an introductory critical essay. Her song lyrics and poetry will be presented in a way to help readers get beyond traditional conventional images of her and gain insight into her originality and importance as a female voice in a literary world of her time that was almost exclusively male.